1997
DOI: 10.1136/gut.40.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Acquired C3 deficiency in patients with alcoholic cirrhosis predisposes to infection and increased mortality.

Abstract: Background-Acquired deficiencies of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 26 publications
2
63
0
6
Order By: Relevance
“…The acquired C3 deficiency in patients with liver cirrhosis could explain an increased risk of infections through a deficit in the capacity of opsonization, although it has been reported that this parameter doesn't appear altered in a stable way in all patients [39,40]. In the study, results support this theory therefore with the worsening of liver function, a directly proportional decrease of these complement components were seen.…”
Section: Discussionsupporting
confidence: 80%
“…The acquired C3 deficiency in patients with liver cirrhosis could explain an increased risk of infections through a deficit in the capacity of opsonization, although it has been reported that this parameter doesn't appear altered in a stable way in all patients [39,40]. In the study, results support this theory therefore with the worsening of liver function, a directly proportional decrease of these complement components were seen.…”
Section: Discussionsupporting
confidence: 80%
“…Diverse studies have demonstrated defects in bactericidal and opsonization capability; low levels have been reported of protein C3 of the complement, as well as deficiencies in the chemotaxis mechanisms [11,12]. To our knowledge, there are no studies to date that have evaluated the capability of neutrophils to release NETs in patients with LC.…”
Section: Discussionmentioning
confidence: 92%
“…Not surprisingly, similarly to individuals with primary deficiency of C3, it has been reported that patients with acquired C3 deficiencies have increased predisposition to infectious disease. (Ram, et al, 2010, Homann, et al, 1997As indicated before, we are aware that further studies with larger cohort are needed to raise definitive conclusions. However, our observation that the only patients in our cohort requiring hospitalization due to infections were two CR1-H/CR1-L heterozygote carriers may be a sign that special attention should be given to PNH patients carrying the CR1-L allele when they are treated with eculizumab.…”
Section: The Observation That Cr1-h/cr1-l Heterozygote Patients Develmentioning
confidence: 99%